Gaya Kognitif Dan Penalaran Verbal Terhadap Prestasi Belajar Mata Pelajaran Penjaskes Di Madrasah Tsanawiyah - Miftakhul Djannah; Moh Choirul Anam; Dian Triana (Arsy : Jurnal Studi Islam, 2022)
This study aims to determine the relationship between cognitive style and verbal reasoning on student achievement in Physical Education subjects. The subjects of this study were 84 students who were cared for and educated at MTsN 10 Jombang in Mojoagung sub-district. The samples were taken randomly, consisting of class VII A = 27 students, class VIII D = 27 students, and class IX B = 30 students. To obtain data regarding the relationship between cognitive style and verbal reasoning on student achievement in Physical Education subjects, a questionnaire prepared by the researcher was used. To achieve this goal, the data were analyzed by coefficient analysis. The results of this study indicate that there is a very significant positive correlation between the application of cognitive style and verbal reasoning on student achievement in Physical Education subjects.